(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
This article focuses on the impoliteness strategies by medical staff of selected public health facilities in Zamfara state. The study interprets and analyses the excerpts of discourse strategies of some medical staff and patients using Culpeper’s (2005) model of impoliteness theory. The data collection methods employed were participant observation and paper recordings. Data were collected from twelve discourse encounters of medical staff and patients from nine (9) public health facilities across the three senatorial zones in the state. Three hospitals were selected from each zone. The data consists of eye-witness events involving the medical staff and patients in the selected health facilities. This research reveals that the language used by some medical staff portrays impoliteness behaviour at varying degrees. The study equally shows that staff of health facilities in the cities mostly employ negative impoliteness strategies while semi-urban hospital staff employ sarcasm or mock politeness in their language use to the patients. The bald on-record impoliteness strategy is employed by health personnel in the rural hospitals while the other impolite strategies are rarely used. Their responses to the patients show an attack on the patients’ face. The article recommends that medical staff shall learn to be polite by using expressions that show sympathy in their talk with the patients who attend public hospitals.